LOCAL ISLAM IN INDONESIA: RELIGION “PATUNTUNG” IN KAJANG - Samiang Katu (JICSA : Journal of Islamic Civilization in Southeast Asian, 2014)
South Sulawesi community, in pra-Islamic society, believed in local believes (creeds) which were so called, the Aluk To Dolo in Tana Toraja, Tolotang in Sidenreng Rappang and Patuntung in Kajang Bulukumba. The Aluk To Dolo in Tana Toraja, since 1972, has been claimed to be an integral part of Hinduism and called Toraja Hindu, while Tolotang has been claimed to be part of the Hindu religion as Hindu To Wani.While adherents ofPatuntungunder the leadership of traditional leaders A m m a T o w a (the Elder Father), still strongly claim that they are adherents of Islam, and are willing to die for the sake of their faith and trust. However, Amma Towa’s belief is somewhat different from Muslim’s in general due to the reference and source of life values of Amma Towa is not Qur'an and al-Sunnah (al-hadith) but Pasang ri Kajang.